Barriers towards furthering of education for migrant youth in South Africa : the case of Musina, Limpopo province - Rapholo, Selelo Frank (Penerbit Universiti Kebangsaan Malaysia, 2021)
Several studies show that the world witnesses the era of unprecedented human mobility. A large number of people, particularly youth, migrate internationally. The international migrant population in Southern Africa is constantly in flux. In South Africa there is a significant struggle for the provision basic social and educational services to the international migrants and this area has not been rigorously explored both in practice and research. The international migrant population have challenges around access to basic education compared to their native peers. It is from this background that this study aimed to explore barriers towards furthering of education amongst migrant youth in South Africa. A qualitative approach with a case study design were used to purposefully select ten (10) migrant youth (5 males and 5 females) in Musina town. Semi-structured individual interviews were used to collect data which was analysed thematically through the assistance of Nvivo software. Findings show that migrant youth are willing pursue studies in South Africa but due to barriers, such as; lack of motivation, unawareness of their constitutional rights to education and local language competency they are unable to do so. It is thus imperative that the education sector in South Africa be robustly empowered about immigration policies on the rights of immigrants’ access to education so as to develop multicultural pedagogies and curricula.